2018
DOI: 10.18699/vj18.431
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the genetic structure of the Kazakh from clan distribution data

Abstract: Applying quasigenetic markers - non-biological traits which are nevertheless inherited in generations - is one of the research fields within human population genetics. For the West European, East European, and Caucasus populations, surnames are typical quasigenetic markers. For Central Asian populations, particularly Kazakh, the clan affiliation serves as a good marker: a set of papers demonstrated that many clans include mainly persons which biologically descent from a recent common ancestor. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…The ancestral haplogroup R1a1a-M198 was found with high frequency in the Shanyshkyly (24%) and Oshakty clans (20%) [ 19 ]. Both clans are found in the Turkestan area [ 28 ], which has the highest frequency of this haplogroup—8.9% in our research. In the same Turkestan area, the fraternal haplogroup R1b1a1a1-M478 shows a significant frequency—5.9% among Kazakhs.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The ancestral haplogroup R1a1a-M198 was found with high frequency in the Shanyshkyly (24%) and Oshakty clans (20%) [ 19 ]. Both clans are found in the Turkestan area [ 28 ], which has the highest frequency of this haplogroup—8.9% in our research. In the same Turkestan area, the fraternal haplogroup R1b1a1a1-M478 shows a significant frequency—5.9% among Kazakhs.…”
Section: Resultsmentioning
confidence: 62%
“…Ysty, on the other hand, has a 74% founder effect inside J1 [ 19 ]. This genus is found in the Zhambyl area [ 28 ], where it is most common (J1—13.8%) in this research.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results of the AMOVA and Mantel tests in our study confirmed that there is significantly less genetic variation among zhuzes than expected under a hierarchical model of genetic structure. This suggests that the zhuz structure is not the primary influence on genetic relationships among Kazakh tribes, and that the division into zhuzes was conditional rather than socio-territorial as suggested by other authors (Ashirbekov et al, 2018;Zhabagin et al, 2018). Nevertheless, approximately, 10% of the genetic variation among individuals was accounted for by variation among zhuzes.…”
Section: Discussionmentioning
confidence: 57%
“…In this type of analysis, three matrices were calculated: (1) a matrix of genetic distances between the kozhuun (territorial units of Tuva); (2) a matrix of geo- (3) a quasi-genetic distance matrix (tribal structure). When calculating the matrix of quasigenetic distances, each clan is traditionally considered as an analog of one allele of the neutral multiallelic locus (quasigenetic marker) [20]. A correlation analysis of these three matrices convincingly showed that the correlation between genetics and the tribal structure is large and reliable (r = 0.50; P < 0.05), while the correlation between genetics and geography is two times smaller and unreliable (average r = 0.25; P > 0.05).…”
Section: Short Communicationsmentioning
confidence: 99%